Determining Factors of Financial Distress in Property and Real Estate Companies Listed on the Indonesia Stock Exchange - Salmiyah Thaha; Indra Diputra; Hariyanti Hariyanti; Mulyana Machmud (Universitas Muhammadiyah Makassar, 2023)
The objective of this study is to investigate the impact of the Current Ratio, Debt to Equity Ratio, and Return On Assets on the occurrence of Financial Distress within Property and Real Estate companies listed on the Indonesia Stock Exchange (IDX) over the period from 2019 to 2021. The study aims to discern whether these factors exhibit an influence, either individually or collectively. The sample selection process employed purposive sampling, leading to the inclusion of 18 companies that met specific criteria. The analytical approach utilized in this study involves multiple linear regression analysis, conducted through the Statistical Package for the Social Sciences (SPSS). The findings indicate that, on an individual basis, the Current Ratio and Return On Assets significantly impact financial distress, whereas the Debt to Equity Ratio exhibits significance in property and real estate companies. Furthermore, when considering all three factors simultaneously, the research demonstrates that the Current Ratio, Debt to Equity Ratio, and Return On Assets collectively exert a significant impact on financial distress within property and real estate sector companies listed on the Indonesia Stock Exchange.